Mental and Sexual Health Outcomes Associated with FGM/C in Africa: A Systematic Narrative Synthesis - Esho, Tammary; Manasi, Kumasi (eClinicalMedicine, 2023)
There are gaps in evidence regarding mental and sexual outcomes and associated interventions for women with Female Genital Mutilation/Cutting (FGM/C) living in Africa. This study employed a narrative synthesis to collate evidence on mental and sexual health outcomes. A systematic search of bibliographic databases and websites was performed using appropriate keywords and studies published in English from January 1, 2010 to March 25, 2022. 25 studies were retrieved and reported mental and sexual health complications associated with FGM/C. Most studies, n = 13 studies reported on sexual health outcomes including sexual pain, orgasm and sexual desire problems at sexual arousal and difficulties in lubrication. Mental health outcomes were reported in four studies including depression which was most prominent followed by somatisation and anxiety, Post Traumatic Stress Disorder (PTSD) and sleep disorder. Studies did not highlight combined mental and sexual health interventions. The findings of this narrative synthesis reveal the need to prioritise provision of mental and sexual health care services for women with FGM/C. The study recommends strengthening of health systems in Africa through awareness building, training and capacity building of primary health and specialist health workers in offering mental and sexual health care to women with FGM/C.
Keywords: FGM; Mental health; Sexual health; Sub-Saharan Africa; Integrated care; Depression and trauma